Parasites of Pieris rapae L. in south-eastern Queensland - Hassan, S. T. (1976)
In spring, the principal parasites of Pieris rapae were Apanteles glomeratus for the larvae, and Pteromalus puparum, Brachymeria regina and Compsilura concinnata for the pupae. The highest level of parasitism by A. glomeratus was 67%, and the highest pupal parasitism was a.pproximately 63% by P. puparum